The effect of soy isoflavones in brain development: the emerging role of multiple signaling pathways and future perspectives - Winda Ariyani; Noriyuki Koibuchi (Endocrine Journal)
Soybean is a source of protein, fibers, and phytochemical isoflavones which are considered to have numerous health benefits for children and adulthood. On the other hand, isoflavones are widely known as phytoestrogens that exert their action via the estrogen signaling pathway. With this regard, isoflavones are also considered as endocrine-disrupting chemicals. Endogenous estrogen plays a crucial role in brain development through binding to estrogen receptors (ERs) or G protein-coupled estrogen receptors 1 (GPER1) and regulates morphogenesis, migration, functional maturation, and intracellular metabolism of neurons and glial cells. Soy isoflavones can also bind to ERs, GPER1, and, furthermore, other receptors to modulate their action. Therefore, soy isoflavone consumption may affect brain development during the pre-and post-natal periods. This review summarizes the current knowledge on the mechanisms of isoflavone action, particularly in the early stages of brain development by introducing representative human, and animal models, and in vitro studies, and discusses their beneficial and adverse impact on neurobehavior. As a conclusion, the soy product consumption during the pre-and post-natal periods under proper range of dose showed beneficial effects in neurobehavior development, including improvement of anxiety, aggression, hyperactive behavior, and cognition, whereas their adverse effect by taking higher doses cannot be excluded. We also present novel research lines to further assess the effect of soy isoflavone administration during brain development.